Impacts of motivation for self-development on job performance in employees of a deluxe hotel in Korea - Shin, Hyoung Chul; Park, Yoon Joo (Nurture, 2024)
Purpose: The aim of this study is to examine the effect of the self-development motivation of Deluxe Hotel employees in Korea on job performance. Design/Methodology/Approach: The current study included 332 subjects who were employees of deluxe hotels located in Korea, for whom a self-reporting questionnaire survey was performed. They were given questionnaires via a mail survey using a judgment sampling method. The selection criteria for the current study were limited to employees who were engaged in the department of foods and beverages or cuisine at deluxe hotels in Korea. Structural equation model analysis was conducted to verify the hypothesis. Finding: The results of this study supported the following hypotheses: “Autonomous motivation has a significant positive impact on job competency,” “Job competency has a significant positive impact on job efficacy”, and “Job efficacy has a significant positive impact on job performance.” Conclusion: The current results indicate that motivation for self-development is an essential factor that may raise employees’ performance and create new opportunities for an organization. Therefore, it would be mandatory to implement effective strategies for motivation and self-development and involve employees in the decision-making process. Thus, dedicated efforts should be made to harmonize an employee’s goals with an organization’s goals.